ANALISIS PENGARUH STRUKTUR MODAL TERHADAP KINERJA KEUANGAN PERUSAHAAN - Achmad Komara; Sri Hartoyo; Trias Andati (University of Merdeka Malang, 2016)
AbstractAt this time, business growth requires proper companys financial strategy, especially by managing the capitalstructure to meet funding need of business operations. This research describes the impact of capital structure onfinancial performance of finance company listed on the Indonesia Stock Exchange during the years 2009-2013. The dependent variable in this study is financial performance composed of return on assets ratio (ROA),return on equity ratio (ROE) and price-to-earnings ratio (PER).While the independent variable in the form ofcapital structure is the ratio of debt to total assets (DAR) and the ratio of debt to total equity (DER). The resultof panel data regression analysis showed that the capital structure has negative significant effect on financialperformance of ROA and ROE, but has positive significant effect on PER. Based on these results, the financecompanies should apply the precautionary principle in managing capital resources coming from debt financing,because the increased component of excessive debt in the capital structure of the company could lead to anincrease in the financial burden that affects the reduction in companys profit.